Locality matters: Variation in the reproductive cycle and population structure of subtropical sea urchins - Raibel Núñez-González; Airam N. Sarmiento-Lezcano; María J. Caballero; Ekin Tilic; José Juan Castro-Hernández (PLoS ONE, 2025)
The life cycle of many Echinoidea species remains poorly understood despite research conducted in temperate and tropical-subtropical regions. Common species in the Central-Eastern Atlantic’s shallow waters include Paracentrotus lividus, Arbacia lixula, and Sphaerechinus granularis. Nevertheless, significant gaps in understanding their life cycles persist. This study discusses the reproductive cycles of three sea urchin species in rocky coastal ecosystems around Gran Canaria Island (Spain) (27º45´N, 15º45´W) from June 2020 to May 2021. Morphological measurements reveal that test length increases without a corresponding weight gain. The average size at first maturity (L50) was greater in females (A. lixula 46.26 mm; P. lividus 46.03 mm; S. granularis 49.67 mm SL) than in males (A. lixula 43.55 mm; P. lividus 42.82 mm; S. granularis 48.57 mm SL). The gonadosomatic index in females exceeded that of males. Histological analysis showed oocytes at various developmental stages, indicating asynchronous ovarian development with successive batch spawning seasons. Reproductive activity was generally observed during the warm season for all three species, likely coinciding with increased nutrient availability in Canarian waters. Notably, P. lividus was the only species to show two reproductive seasons annually in San Cristobal. DNA analysis confirmed species identification and provided new fragments of the COI gene, now available in GenBank for future population analysis. These findings represent the first reproductive data for these species in the North Atlantic region, offering valuable insights into their populations and establishing baseline information for managing sea urchin populations.